Strategic Role Of Digital Marketing In Increasing Purchase Intention For Vocational Education Based Teaching Factory Products - Prawidya Destarianto; Ginta Ginting (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study examines the possible influence of digital marketing on consumer purchasing intentions for Teaching Factory JTI Innovation products at Jember State Polytechnic. The study was initiated by a growing need to improve the competitiveness and sustainability of vocational education products through more adaptable and technology-based marketing approaches. For this purpose, a Systematic Literature Review (SLR) was carried out, analyzing 32 high-quality academic articles to identify the most influential determinants of purchase intention in the context of digital marketing. The evaluation focuses on multiple interconnected aspects, including the marketing mix, human resource competency, brand trust and awareness, digital media efficacy, and consumer psychology behavior. Digital media performance, brand reliability, and consistent implementation of an integrated marketing mix emerge as the most important factors influencing consumer willingness to purchase a product. Although it has benefits, the research identifies significant barriers to the efficient application of digital marketing strategies in vocational education institutions, including poor digital literacy, limited brand exposure, and insufficient technological infrastructure. Based on these findings, the study recommends several strategic directions: institutions should maximize the use of digital media platforms, develop research-based brand positioning for their innovative products, and improve digital literacy among lecturers and students to strengthen institutional marketing capacity. In conclusion, the study provides a theoretical contribution by improving the knowledge of digital marketing's role in influencing purchase behavior within the educational innovation ecosystem, in addition to a practical contribution by providing evidence-based recommendations to improve marketing performance, product visibility, and the long-term viability of Teaching Factory initiatives in vocational higher education.